Partnering with Parents in Support of Student Persistence in Canadian Higher Education - Jennifer Sparks (Canadian Society for Studies in Education, 2019)
Student persistence is a challenge in Canadian higher education. Fortunately, parent involvement can encourage students to persist in their post-secondary studies. The following paper recommends that Canadian higher education institutions partner with parents of students by informing students and their parents of the realities of student persistence via program switches, school transfers, leaves of absence, withdrawal and re-enrollment (plan Bs). In partnering with parents of students, Canadian higher education institutions may help students to obtain the additional support they need to persist via alternative credential completion pathways.